1 John Ray, Digest of the Statutes of the State of Louisiana 387 (1870) - (:unkn) unknown (My University, 1870)
If any person shall voluntarily engage in a duel with rapier or small sword, back sword, pistol or other dangerous weapon to the hazard of life, and death shall ensue, the survivor shall, upon conviction, suffer death; and all and every person aiding and abetting as second, agent or abettor, shall, on conviction, be punished as accessories before the fact in murder
Keywords: DUELING